The digger wasps of the genus Alysson Panzer (Hymenoptera: Crabronidae: Bembicinae) of Russia and adjacent territories, with a key to species and new synonymies - Nemkov, Pavel G. (Zootaxa, 2014)
Nine species of Alysson Panzer 1806 are recorded from Russia and adjacent territories. The new synonymy is proposed for Alysson pertheesi Gorski 1852 =A. fuscatus var. jaroslavensis Kokujev 1906, =A. harbinensis Tsuneki 1967; Pompilus spinosus (Panzer 1801) =Alysson katkovi Kokujev 1906. The number of valid species-group taxa in the genus Alysson is reduced to 39 species. An original key to the species is provided.